1988
DOI: 10.1002/jctb.280410403
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acids and cellulase enzyme for the effective hydrolysis of agricultural lignocellulosic residues

Abstract: This paper reports the results of experimentation carried out to compare the ability of mineral acids (HCl and H2SO4) and cellulase enzyme (from Trichoderma reesei QM 9414) in the saccharification of corn‐cob, groundnut shell, sugarcane bagasse and wheat straw. With the exception of corn‐cobs, acids proved to be better saccharifying agents than the cellulase complex, but the former gave a poor substrate for alcoholic fermentation since the saccharified mashes contained large amounts of pentoses which are not m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…Essentially, cell wall digestibility by acids or enzymes depends upon the arrangement of lignin network with the structural carbohydrates in the cell wall. Tewari et al (1988) found the requirement of more acid load (15% v/v H 2 SO 4 ) and residence time of 15 min for hemicelluloses hydrolysis of GS compared to less acid load (5% v/v H 2 SO 4 ) to hydrolyse sugarcane bagasse and corn cob at 15 Psi for 30 min. The order of enzymatic hydrolysis efficiency was also recorded lowest with GS.…”
Section: Delignification and Enzymatic Hydrolysismentioning
confidence: 97%
“…Essentially, cell wall digestibility by acids or enzymes depends upon the arrangement of lignin network with the structural carbohydrates in the cell wall. Tewari et al (1988) found the requirement of more acid load (15% v/v H 2 SO 4 ) and residence time of 15 min for hemicelluloses hydrolysis of GS compared to less acid load (5% v/v H 2 SO 4 ) to hydrolyse sugarcane bagasse and corn cob at 15 Psi for 30 min. The order of enzymatic hydrolysis efficiency was also recorded lowest with GS.…”
Section: Delignification and Enzymatic Hydrolysismentioning
confidence: 97%
“…Posterior al pretratamiento de la cascarilla de arroz, se realiza la hidrólisis enzimática, mediante una mezcla de enzimas que constan principalmente de celulasas, ß-glucosidasas y hemicelulasas de tipo xilanasas 12,13 . Como una medida de la eficiencia de la hidrólisis, se utiliza el parámetro de la sacarificación, que relaciona el contenido de los azúcares reductores en el hidrolizado con el contenido de azúcares totales en la cascarilla de arroz 12,14,15,16 .…”
Section: Introductionunclassified
“…Buscando a verificação do diâmetro médio de partículas do bagaço costumeiramente utilizada por pesquisadores em estudos da hidrólise enzimática, foi realizada uma pesquisa na base SCOPUS utilizando a seguinte sequencia de palavras-chave: "hydrolysis and sugarcane", refinando com "bagasse", novamente com "ethanol" e, por último, com "enzyme". Homogeneizado (Processador de alimentos), peneirado (30-45mesh) 0,600 -0,354 KUO et al, 2009 Peneirado (20 -40 mesh) 0,850 -0,425 CHENG et al,2008 Moagem e peneiramento (20 mesh) 0,850 TEWARI et al,1988 Moído usando um moedor de café comercial e peneirado (20 mesh) 0,850 LEE et al, 2009 Moído e peneirado 0,900 ZHAO et al, 2009 Moído e peneirado (20-mesh) 0,900 ZHAO et al, 2008 Moído e Peneirado 0,900 ZHAO et al, 2007 Moído 0,900 KAEWINTAJUK et al, 2006 Não Informado 0,900 ZHENG et al, 2002 Moído até passar pela peneira de 1 mm (moinho de bolas TI-300) 1,000 BUABAN et al, 2010 Moído, peneirado, selecionado (28 -42 mesh) 1,163 DE CASTRO et al, 2010 Uma parte moído sem peneiramento e outra parte moído após peneiramento (12 -60 mesh) 1,397 -0,248 RABELO et al, 2009 Moído em pequeno moinho de disco e peneirado 1,680 -0,149 HERNANDEZ-SALAS et al, 2009 Moído até passer por uma peneira de abertura 2 mm 2,000 MARTIN et al, 2008;MARTIN et al, 2007(a); MARTIN et al, 2007(b) Cortado em pequenos pedaços de 1-3 mm 3,000 -1,000 ADSUL et al, 2007 Fracionado em um tamanho entre 2.2 e 10 mm 10,000 -2,200 MARTIN et al, 2002(a); MARTIN et al, 2002(b) Moído, utilizando as partículas menores que 12 mm 12,000 PRIOR et al, 2008 Pela Tabela 02 deduz-se que os pesquisadores têm preocupação em reduzir o tamanho das partículas de bagaço, porém não existe um padrão para o tamanho escolhido nem um método comum de pré-tratamento físico.…”
Section: Medulaunclassified